2000
DOI: 10.1034/j.1600-079x.2000.290201.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term daily melatonin infusion induces a large increase in N‐acetyltransferase activity, hydroxyindole‐O‐methyltransferase activity, and melatonin content in the Harderian gland and eye of pinealectomized male Siberian hamsters (Phodopus sungorus)

Abstract: The effects of long-term daily melatonin infusions on the melatonin synthetic pathway in the Harderian glands and eyes of male Siberian hamsters were studied. Hamsters were pinealectomized (PX) and infused daily for 8 hr with either melatonin (6 microg/hr) or vehicle for 7 days in short photoperiod (SP, 10L:14D), followed by 14 wk in either SP (SP group) or in constant darkness (DD group). After the infusion period (15 wk), the infusion was stopped and animals were transferred into SP for 3 wk. The hamsters we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…The MEL profile showed a relatively high basal level. Recently, it was reported that chronic MEL infusion enhanced the ability of the Harderian gland to produce MEL, thus leading to an increased basal level of the hormone in the Djungarian hamster [20]. Such a mechanism might explain the elevated basal level in our study, because the MEL-producing Harderian gland also exists in the rat [21].…”
Section: Treatment Administration Data Recording and Analysissupporting
confidence: 56%
“…The MEL profile showed a relatively high basal level. Recently, it was reported that chronic MEL infusion enhanced the ability of the Harderian gland to produce MEL, thus leading to an increased basal level of the hormone in the Djungarian hamster [20]. Such a mechanism might explain the elevated basal level in our study, because the MEL-producing Harderian gland also exists in the rat [21].…”
Section: Treatment Administration Data Recording and Analysissupporting
confidence: 56%
“…Our results are in accordance with other authors who have demonstrated that oral administration of melatonin to patients with type 2 diabetes or primary essential hypertension correlates with the increased antioxidant capacity of plasma (KedzioraKornatowska et al 2008(KedzioraKornatowska et al , 2009). Similarly, infusion or oral administration of melatonin precursor L-tryptophan caused a dose-dependent increase of endogenous melatonin level in plasma (Djeridane et al 2000;Jaworek et al 2007). In the present study, because the volunteers were banned from intake of other antioxidants, the increase in FRAP value could be related to enhancing the synthesis of melatonin after oral supplementation of the hormone.…”
Section: Discussionmentioning
confidence: 99%
“…This organ is presumed to serve as an extraretinal phototransducer involved in the retinal± pineal axis (in Payne, 1994) and is intimately associated with eyes and opens by a duct onto the surface of the nictitating membrane (Sakai, 1981;Djeridane, 1992Djeridane, , 1994Djeridane, , 1996. In rodents, the Harderian gland synthesizes lipids (Seyama et al, 1992), photosensitive porphyrin pigments (Spike, Payne and Moore, 1992), and indoles (MenendezPelaez and Buzzell, 1992;Menendez-Pelaez et al, 1993;Djeridane et al, 1999a,b), mainly melatonin (Djeridane et al, 1998(Djeridane et al, , 2000. The organs also exhibit activity of serotonin N-acetyltransferase (NAT) and hydroxyindole-O-methyltransferase (HIOMT), enzymes necessary for melatonin production (Pe Âvet et al, 1980;Balemans et al, 1983;Menendez-Pelaez and Buzzell, 1992;Menendez-Pelaez et al, 1993).…”
Section: Introductionmentioning
confidence: 97%